### Home > CAAC > Chapter 13 > Lesson 13.RE3-S > Problem 2-149

2-149.

Rewrite each equation below. Then solve your new equation. Be sure to check your solution using the original equation. Homework Help ✎

(

*n*+ 4) +*n*(*n*+ 2) +*n*= 0

Distribute the *n*.

Combine like terms, and factor the equation.

Simplify by Zero Product Property, then subtract 2 from both sides.

Remember to check your work.

*n* + 4 + (*n*^{2} + 2*n*) + *n* = 0

*n*^{2} + 4*n* + 4 = 0

(*n* + 2) (*n* + 2) = 0

*n* + 2 = 0

*n* = −2

Multiply both sides by *x*. Then set the equation equalto 0 and use the ZPP.

*x* = −4 or *x* = 1

Check your work.